2021
DOI: 10.1038/s41467-021-27513-z
|View full text |Cite
|
Sign up to set email alerts
|

KRas-transformed epithelia cells invade and partially dedifferentiate by basal cell extrusion

Abstract: Metastasis is the main cause of carcinoma-related death, yet we know little about how it initiates due to our inability to visualize stochastic invasion events. Classical models suggest that cells accumulate mutations that first drive formation of a primary mass, and then downregulate epithelia-specific genes to cause invasion and metastasis. Here, using transparent zebrafish epidermis to model simple epithelia, we can directly image invasion. We find that KRas-transformation, implicated in early carcinogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 40 publications
6
37
0
Order By: Relevance
“…Although apical cell extrusion is a defense mechanism of epithelia, transformed cells can hijack this mechanism to facilitate invasion. In zebrafish epidermis KRAS V12 mutation induces basal extrusion, facilitating invasion beyond the epithelium [54].…”
Section: Emt and Single-cell Invasionmentioning
confidence: 99%
“…Although apical cell extrusion is a defense mechanism of epithelia, transformed cells can hijack this mechanism to facilitate invasion. In zebrafish epidermis KRAS V12 mutation induces basal extrusion, facilitating invasion beyond the epithelium [54].…”
Section: Emt and Single-cell Invasionmentioning
confidence: 99%
“…Importantly, oncogenic Ras is a potent suppressor of apoptosis in flies and mammalian tissues [73]. While this prevents elimination of these cells from imaginal discs, these cells are eliminated from mammalian tissue, however importantly: by a cell death independent mechanism that involves strong activation of interfacial actomyosin activity, driving mechanical squeezing out of the tissue layer [68][69][70][74][75][76][77][78]. We thus suggest that interface contractility and EDAC are evolutionarily conserved expression of the same ancient tissue-intrinsic defence system that specifically acts against cell fate deregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is the dominant cause of advanced tumor stage (66), and enhanced cell invasion and migration and PCGEM1 overexpression have been observed in diverse cancer cell lines. Zhang et al ( 43) revealed that PCGEM1 facilitates GC cell invasion and metastasis via the miR-129-5p/prolyl 4-hydroxylase subunit alpha 2 (P4HA2) axis (43).…”
Section: Cell Motilitymentioning
confidence: 99%
“…Metastasis is the dominant cause of advanced tumor stage ( 66 ), and enhanced cell invasion and migration and PCGEM1 overexpression have been observed in diverse cancer cell lines. Zhang et al.…”
Section: Functions Of Pcgem1 and Underlying Mechanismsmentioning
confidence: 99%